Exclusive Image Gallery on Human Spinal Cord Regeneration-Clinical Image-48 - Giselher Schalow (Imaging Journal of Clinical and Medical Sciences - Peertechz Publications, 2019)
Improvement of urinary bladder functioning quantified by the time from the urge/desire to void until micturition.